2015
DOI: 10.3389/feart.2015.00082
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Impurities on the Surface Melt of a Glacier in the Suntar-Khayata Mountain Range, Russian Siberia

Abstract: We investigated characteristics of impurities and their impact on the ablation of Glacier No.31 in the Suntar-Khayata Mountain Range in Russian Siberia during summer 2014. Positive degree-day factors (PDDFs) obtained from 20 stake measurements distributed across the glacier's ablation area varied from 3.00 to 8.55 mm w.e. K −1 day −1 . The surface reflectivity measured with a spectrometer as a proxy for albedo, ranged from 0.09 to 0.62, and was negatively correlated with the PDDF, suggesting that glacier ablat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…Experimental results presented here, together with previous correlative observations [8][9][10][11][12][13][14][15][16] , laboratory experiments 17 , and theoretical calculations 18 , provide a compelling case for the magnitude of the glacier microbiome's effect on hydrology and climate. Snow algae amplify their albedo reduction through life history, population growth, dispersal, and physiology.…”
Section: Implications For High-latitude Ice Sheetssupporting
confidence: 62%
See 3 more Smart Citations
“…Experimental results presented here, together with previous correlative observations [8][9][10][11][12][13][14][15][16] , laboratory experiments 17 , and theoretical calculations 18 , provide a compelling case for the magnitude of the glacier microbiome's effect on hydrology and climate. Snow algae amplify their albedo reduction through life history, population growth, dispersal, and physiology.…”
Section: Implications For High-latitude Ice Sheetssupporting
confidence: 62%
“…The generation of meltwater through microbes' albedoreducing properties motivates an hypothesis of bio-geophysical feedback on glacial landscapes 13,16 , such as the Greenland ice sheet. This feedback hypothesis, whereby microbes increase because they produce needed meltwater, is an active research area [13][14][15][16][17][18][19] , yet field experiments testing its assumptions are absent.Glacier microbiomes are water-limited 21,22 , because ice is generally not metabolically available, and oligotrophic, because their nutrient content equals that of precipitation plus deposition by airborne dust, pollen, and so on, with only limited N-fixation by local cyanobacteria 21,22 . Moreover, rapidly percolating water through large-grained snow may exacerbate both water-and nutrient limitation for algae in supraglacial snow-covered habitat 7 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Lutz et al, 2016), which is unsurprising, since the majority of the variation in albedo is due to physical characteristics of the snow or ice including internal factors such as ice crystal size and water content as well as external factors such as solar angle, atmospheric effects, shading and multiple reflections between surface roughness elements (Gardner and Sharp, 2010). Takeuchi (2002), Takeuchi and Kohshima (2004) and Takeuchi et al (2015) showed the albedo reduction resulting from biotic and abiotic impurities to vary between different glaciers, signifying that the mass and optical properties of abiotic impurities such as dust are also crucial determinants of surface albedo. This may be particularly relevant on the western Greenland Ice Sheet, where high concentrations of dust may be outcropping from melting Holocene ice (Bøg-gild et al, 2010;Wientjes et al, 2010Wientjes et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%